Macular Amyloidosis with Atypical Clinical Manifestation and Its Dermoscopic Correlation; [Amiloidosis Macular Con Manifestación Clínica Atípica y Su Correlación Dermatoscópica] - Chavez-Rojas, F (Ediciones Doyma, S.L., 2024)
[No abstract available]